Oxidative Telomere Attrition, Nutritional Antioxidants and Biological Aging - Glade, Michael J. (International Journal of Nutrition, 2015)
Telomeres are strings of DNA that are not themselves genes but that extend every chromosome beyond its last gene. Terminal telomeres are sacrificed during every mitotic event in human cells (“telomere attrition”), preserving the functional genome despite the “end replication problem.” However, the “telomeric theory of biological aging” suggests that when an individual cell has reproduced itself a sufficient number of times (the “Hayflick limit”), some the its telomeres have become critically shortened (“telomeric crisis”) and cannot completely “cap off” a chromosome, and any further attempts to replicate such a chromosome would produce damaged DNA and a dysfunctional cell (“cellular aging”). As cells enter telomeric crisis, they usually initiate intracellular signaling cascades that arrest DNA replication and mitotic activity, converting biologically active cells into inactive cells (“cellular senescence”). The progressive accumulation of senescent cells impairs the healthy functioning of tissues and produces “biological aging.” Oxidative stress damages telomeres and accelerates telomere attrition and biological aging. Premature biological aging is associated with degenerative diseases and diminished quality of life. Reducing the level of systemic oxidative stress can ease the oxidative drive toward cellular senescence and premature biological aging. Increased intakes of antioxidant-rich foods and specific antioxidant nutrients (such as fruits and vegetables, α -lipoic acid, astaxanthin, eicosapentaenoic acid, docosahexaenoic acid, trans-resveratrol, N-acetylcysteine, methylsulfonylmethane, lutein, vitamin C, vitamin D, vitamin E, and γ-tocotrienol) may decrease cellular and systemic oxidative stress and decelerate biological aging.
Keywords: Telomere attrition; biological aging; cellular senescence; nutrients; oxidative stress; antioxidants